Luxury and Rubble: Civility and Dispossession in the New Saigon - Harms, Erik (University of California Press, 2016)
Luxury and Rubble is the tale of two cities in Ho Chi Minh City. It is the story of two planned, mixed-use residential and commercial developments that are changing the face of Vietnam's largest city. Since the early 1990s, such developments have been steadily reorganizing urban landscapes across the country. For many Vietnamese, they are a symbol of the country's emergence into global modernity and of post-socialist economic reforms. However, they are also sites of great contestation, sparking land disputes and controversies over how to compensate evicted residents. In this penetrating ethnography, Erik Harms vividly portrays the human costs of urban reorganization as he explores the complex and sometimes contradictory experiences of individuals grappling with the forces of privatization in a socialist country.